2007
DOI: 10.1152/ajpregu.00622.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypobaric hypoxia exposure does not cause sustained alterations in autonomic control of blood pressure in young athletes

Abstract: Intermittent hypoxia (IH), which refers to the discontinuous use of hypoxia to reproduce some key features of altitude acclimatization, is commonly used in athletes to improve their performance. However, variations of IH are also used as a model for sleep apnea, causing sustained sympathoexcitation and hypertension in animals and, thus, raising concerns over the safety of this model. We tested the hypothesis that chronic IH at rest alters autonomic control of arterial pressure in healthy trained individuals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 57 publications
5
31
1
Order By: Relevance
“…Consistent with previous reports, following exposure to IH of similar duration (8,22,27), baseline cardiorespiratory and cerebrovascular variables were unchanged. The lack of change in cardiovascular measurements (BP, heart rate, cardiac output) at rest is consistent with recent reports (10,27), indicating an absence of change to autonomic control. During hypoxic but not normoxic exercise, following both IH and CH, there was a greater elevation in Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous reports, following exposure to IH of similar duration (8,22,27), baseline cardiorespiratory and cerebrovascular variables were unchanged. The lack of change in cardiovascular measurements (BP, heart rate, cardiac output) at rest is consistent with recent reports (10,27), indicating an absence of change to autonomic control. During hypoxic but not normoxic exercise, following both IH and CH, there was a greater elevation in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The chronic (i.e., years) repetitive and brief "apneas" associated with obstructive sleep apnea cause hypoxia, hypercapnia, and asphyxia, all of which contribute to sympathoexcitation (6), which seem critical to evoke adverse vascular changes. It should be acknowledged that comparable hypoxiato-reoxygenation cycles do not occur during the "typical" IH protocols used for athletic training [e.g., 5:5-min hypoxia-tonormoxia for 60 -90 min/day (2,8), or 30 min to 3 h continued hypoxia/day (10)] or by researchers as interventions to examine the potential consequences on systemic and cerebrovascular function (8,10,27,44). For example, during a typical 5:5-min hypoxia-to-normoxia session for 60 min or during a 1-h hypoxic exposure, the episodes of hypoxia to normoxia will be 6/h and 1/h, respectively; this represents very different conditions to Ͼ50 apneic events/h in a patient with moderate to severe obstructive sleep apnea.…”
Section: Differential Alterations In Cerebral and Muscle Oxygenation mentioning
confidence: 99%
“…Whilst comparison between studies is difficult, the comparable decrease in cerebral oxygenation at maximal exercise in the current study was more likely a consequence of the related hypocapnic-induced lower cerebral perfusion, rather than an intrinsic alteration in cerebrovascular function. Moreover, the unchanged heart rate response throughout the IHE are consistent with a recent report which also showed that autonomic control is unaltered following exposure to intermittent hypoxia (Fu et al 2007). …”
Section: Effects Of Ihe On Gas Exchangesupporting
confidence: 91%
“…The degree of hypoxia was about 12% or equivalent to about 4,000 m at least when starting exposures [3][4][5][6][7]. Most studies exposed subjects at rest to hypoxia [8][9][10][11][12][13][14][15][16][17][18][19]. Those comparing the effects when exposures were at rest or with exercise did not find any differences [5,6].…”
Section: Resultsmentioning
confidence: 99%